Microfacies and Palaeoenvironment of Avanah Formation (Middle Eocene) Geli Bessri in Dohuk City / North of Iraq - Mustafa A. Abdullah; Faris N. Hassan; Abdulsalam. M.Saleh (Tikrit Journal of Pure Science)
This research is based on (23) Samples selected from the Avanah Formation (Middle Eocene) in the Geli Bessri section in Dohuk to recognize the microfacies and depositional environments. The Avanah Formation consists of rocks of marly limestone and limestone containing Alveolina and thin layers of sandstone lithofacies found in the lower part of the Formation. The depositional environment was determined depending on skeletal and non- skeletal grains. The facies of the Avanah Formation were divided into four main microfacies and four submicrofacies based on skeletal and non- skeletal grains: The mudstone and wackestone, which is divided into benthic foraminifera wackestone and Rotaliids wackestone, the Formation also contains the packstone which is divided into the Rotaliid - Miliolid Lime packstone submicrofacies and benthic foraminifera lim packstone submicrofacies, in addition to the lime grainstone and also contains the Sandstone lithofacies located at the bottom of the Formation. The Avanah Formation in the middle and upper part is subjected to diagenesis process early dolomization and it is observed this through floating dolomite rohmb. According to the results of the facies analysis and the presence of foraminifera fossils, the Formation was deposited in open marine platform to restricted platform interior.